Tattoo Regret, Complications, and Removal: A Cross-Sectional Study among Tattooed Individuals in Saudi Arabia - Hadeel Mitwalli; Nuha Alfurayh (Dermatology Research and Practice)
Background. A tattoo is a pigment permanently deposited into the skin to create different patterns. The worldwide percentage of tattooed individuals, as well as the level of tattoo regret, complications, and removal, has increased. However, data from Saudi Arabia are lacking. Objective. To determine the rates of tattoo regret, complications, and removal among tattooed individuals in Saudi Arabia. Methods. A cross-sectional study using an online survey was conducted in Riyadh, Saudi Arabia. A link to the survey was distributed through social media and contained twenty questions about participants’ demographics, tattoo practices, regret, removal, and complications. Data were analyzed using the Statistical Package for Social Sciences (SPSS). A P value <0.05 was considered statistically significant. Results. A total of 181 tattooed individuals participated in the study. Most of them were females (95.6%), and 76.7% had their first tattoo at an age over eighteen years. A total of 47.5% had one tattoo session, and the most common body site was the eyebrows (57.5%). Fifty-eight percent regretted their tattoo, and 42.5% attempted to remove it. Upper extremity tattoos were significantly associated with regret (72.3%) (P=0.004) and removal (56.9%) (P=0.003). Tattoo removal was mostly due to cultural reasons (74%). Local itching (32%), pain (22.7%), and infection (10.5%) were reported and associated with tattoo regret (P<0.05). Itching was significant in 65.4% of head and neck tattoos and 41.5% of upper extremity tattoos (P<0.05). Participants were aware that laser is the best method for tattoo removal. Conclusion. Among tattooed individuals in Saudi Arabia, the rate of tattoo regret and removal is high, and the most reported complication is pruritus.